2005
DOI: 10.1001/jama.293.22.2746
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Infection in Health Care Workers in Rural India

Abstract: N ESTIMATED ONE THIRD OF the world's population is infected with Mycobacterium tuberculosis, 1 presenting a major impediment to tuberculosis control. Despite the importance of latent tuberculosis infection (LTBI), the tuberculin skin test (TST) was, until recently, the only test available for its diagnosis. [2][3][4][5] The TST measures hypersensitivity response to purified protein derivative (PPD), a crude mixture of antigens, many of which are shared among M tuberculosis, Mycobacterium bovis bacille Calmette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
98
8
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(134 citation statements)
references
References 26 publications
23
98
8
5
Order By: Relevance
“…Our results with an overall high percent agreement between TST and IFN-␥ assay with low are consistent with and support the findings by other studies that have reported overall agreements of 81.4 to 95.0% with values of 0.08 to 0.87 (8,23,29,30). Kappa statistics have been accepted and widely used as a test of interobserver agreement (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results with an overall high percent agreement between TST and IFN-␥ assay with low are consistent with and support the findings by other studies that have reported overall agreements of 81.4 to 95.0% with values of 0.08 to 0.87 (8,23,29,30). Kappa statistics have been accepted and widely used as a test of interobserver agreement (16).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, IFN-␥ assays utilizing ESAT-6 and CFP-10 either as recombinant antigens (5,7,38) or mixtures of overlapping peptides (8,27,37) have been shown to be significantly more specific than TST. In addition, these assays offer several advantages over TST, including the need for only a single patient contact, simultaneous measurement of a subject's immune reactivity to mitogen (phytohemagglutinin) and nil control (normal saline) antigens, elimination of subjectivity in administering the test or reading the result, and the availability of test results within 24 h. IFN-␥ assays utilizing ESAT-6 and CFP-10 antigens have been studied in the general population in several countries including India, Korea, Italy, Denmark, The Netherlands, and Japan (5,7,8,15,23,27,29,30,38). To date, there are no published reports on comparison of TST to the newly approved IFN-␥ assay in studies within the United States.…”
mentioning
confidence: 99%
“…Perhaps most intriguing was our finding that in the blood, ESAT-6-specific IFN-␥ production could not distinguish M. tuberculosis-infected susceptible CBA/J mice from noninfected mice. The same pattern can also be observed in humans, for whom peripheral-blood IGRAs failed to detect small proportions of M. tuberculosisinfected individuals (18,37) and TB patients (45) bovis BCG vaccination of calves (59) and relatively resistant C57BL/6 mice (17) showed decreased ESAT-6-specific IFN-␥ blood responses, likely reflecting antigenic loads lower than those of nonvaccinated control animals. Because CBA/J, DBA/2, and C3H/HeJ mice had low circulating ESAT-6 responses during primary M. tuberculosis infection, we predict minimal changes due to BCG vaccination, antibiotic treatment, or immunosuppression.…”
supporting
confidence: 57%
“…The specificity of the ELISPOT-MTP assay was confirmed by the fact that 100% of the ELISPOT-MTP positive subjects were ELISPOT-BCG positive and 97% were ELISPOT-PPD positive. Conversely, the fact that 76% of the ELISPOT-MTP negative subjects were ELISPOT-BCG positive and 59% were ELISPOT-PPD positive supports the idea that most contacts may be vaccinated (Table 1) or NTM infected, thus underlining the greater sensitivity of the ELISPOT assay over the TST, as has also been reported by others (20,28,32,34). Of note, 44 of the 67 individuals with a documented BCG scar were ELISPOT-MTP negative but ELISPOT-BCG positive.…”
Section: Discussionsupporting
confidence: 71%